2013
DOI: 10.1093/carcin/bgt098
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 modulates paclitaxel and epirubicin resistance and survival in breast cancer

Abstract: In this study, we report the identification of a novel role of SIRT6 in both epirubicin and paclitaxel resistance in breast cancer. We found that SIRT6 protein levels are elevated in paclitaxel- and epirubicin-resistant MCF-7 cells compared with the parental sensitive cells. SIRT6 knockout and depletion sensitized cells to both paclitaxel and epirubicin treatment, whereas SIRT6 ectopic overexpression led to increased resistance to paclitaxel and epirubicin. Moreover, our data suggest that SIRT6 could be mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(135 citation statements)
references
References 46 publications
6
127
2
Order By: Relevance
“…For example, it has been demonstrated that SIRT1 can antagonize the p300-mediated acetylation and activation of FOXO3a (21). In agreement, studies conducted in breast cancer have also showed that SIRT6 overexpression correlates with FOXO3a inactivation and that SIRT6 depletion sensitizes breast cancer cells to both paclitaxel and epirubicin treatments (22).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…For example, it has been demonstrated that SIRT1 can antagonize the p300-mediated acetylation and activation of FOXO3a (21). In agreement, studies conducted in breast cancer have also showed that SIRT6 overexpression correlates with FOXO3a inactivation and that SIRT6 depletion sensitizes breast cancer cells to both paclitaxel and epirubicin treatments (22).…”
Section: Introductionmentioning
confidence: 69%
“…FOXO3a nuclear localization is associated with phosphorylation on Ser-7 and acetylation on Lys-242/245 in B-ALL cells Acetylation has been described to modulate the transcriptional activity of FOXO3a (22,40). In addition, a recent study has also demonstrated that JNK phosphorylation can promote FOXO1 acetylation and activation (41).…”
Section: Mw (Kda)mentioning
confidence: 98%
See 1 more Smart Citation
“…Mammals have seven sirtuins, with sirtuin (SIRT) 1-3 exhibiting strong NAD + -dependent deacetylation activity, whereas SIRT4-7 exhibit strong deacetylation and are more accurately described as NAD + -dependent deacylases (77). SIRT2 is predominantly localized in the cytoplasm, whereas SIRT3, SIRT4 and SIRT5 are predominantly in the mitochondria, and SIRT1, SIRT6, SIRT7 in the nucleus (78). FOXO proteins are deacetylated by HDACs and sirtuins simultaneously.…”
Section: Acetylation Of Foxo Proteinsmentioning
confidence: 99%
“…In mouse embryonic fibroblasts, SIRT6 inhibition can increase the acetylation level of FOXO3a. However in breast cancer cells, overexpression of SIRT6, which reduces the acetylation level of FOXO3a, weakens the transcription activity of FOXO3a and generates resistance to epirubicin and paclitaxel, which suggests that inhibition of SIRT6 to upregulate the activity of FOXO3a may be a promising therapeutic strategy for breast cancer (78).…”
Section: Acetylation Of Foxo Proteinsmentioning
confidence: 99%